Risk Factors of Stunting in Children Aged 6-59 Months: A Case-Control Study in Horticulture Area - Prayudhy Yushananta; Mei Ahyanti; Yetti Anggraini (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background. Stunting is a critical public health problem in Indonesia because it affects cognitive andphysical development and contributes to child mortality. This study aims to identify risk factors for stuntingin children aged 6-59 in the horticultural area. Methods. A case-control study was conducted to compareprevious exposure between stunted children and non-stunted children. Measurements and interviews wereconducted with 160 participants (120 controls and 40 cases), including mothers or caregivers. SPSS wasused for X2 statistical analysis, multiple logistic regression, and odds ratios. Results. The study identifiedfour risk factors for stunting: children who were born short (AOR = 17.57; 95% CI: 5.02-61.51), LBW(AOR = 4.35; 95% CI: 1.38-13, 78), and got a low protein intake (AOR = 4.96; 95% CI: 1.22-20.26).Significantly, a relationship between stunting and access to sanitation was also found (AOR = 6.06; 95%CI: 1.25-29.35). Conclusion. The risk factors for stunting in children aged 6-59 are related to nutritionduring pregnancy and the child’s quality of food. Nutrition interventions should emphasize improving thenutritional status of pregnant women and children and women empowering to affect access to resources andallocations for children’s nutrition.